Interpretation of the Song "Selalu Ada di Nadimu" Among Junior High School Students in Pontianak - Jeane, Bernadeta; Djau, Nurmila Sari; Sagala, Mastri Dihita (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to describe junior high school students' interpretations of the meaning of the song "Selalu Ada di Nadimu," the original soundtrack (OST) of the film Jumbo, and to examine how cognitive and emotional processes play a role in their interpretations. The researcher employed a qualitative approach with data collection techniques including song playback, distribution of open-ended questionnaires, brief observations, and documentation. The research subjects consisted of seventh and eighth grade students from two schools in Pontianak City, namely SMP Negeri 3 Pontianak and SMP Kristen Immanuel Pontianak, with a total of 121 students whose responses were successfully collected. The results of the study indicate that students’ interpretations of the song "Selalu Ada di Nadimu" reflect four main patterns in their interpretive processes. First, interpretations based on personal experience constitute the largest category, with many students relating the song’s lyrics to their life experiences, struggles, and self-motivation. Second, emotional responses emerge through feelings of sadness and memories of family. Third, cognitive understanding of the lyrical message is reflected in students’ explanations about parental love and support. Fourth, moral values appear, such as the importance of appreciating family and not giving up easily. These findings show that students interpret the song through a combination of personal experiences, emotions, and their ability to understand the lyrics. This study emphasizes that songs can serve as learning media that support adolescents’ cognitive and emotional development, particularly in helping students develop the ability to understand messages, interpret texts, and connect lyrics with their personal experiences.